The Grifola frondosa-derived ACE inhibitory peptide attenuated the exosomes-mediated phenotype transformation of vascular smooth muscle cells - Tianyuan Song; Tiantian Zhang; Qiaolin Cai; Yin-Yi Ding; Qing Gu; Zhenyu Gu (Journal of Functional Foods, 2024)
Grifola frondosa, a high-protein edible mushroom, exhibited potential antihypertensive effects through ACE inhibition. The ACE was expressed in vascular smooth muscle cells (VSMCs) and transported via exosomes. This study prepared low molecular weight GFP through enzymatic hydrolysis, showing strong ACE inhibition. Ang II increased ACE expression and activity in VSMCs, inducing phenotype switching by up-regulating α-SMA and OPN. GFP reduced Ang II’s stimulating effects. Exosomes from Ang II-treated (Ang II-Exos) or GFP-treated (GFP-Exos) VSMCs had particle sizes under 200 nm with positive biomarkers CD63 and Tsg101. Co-culture experiments revealed higher ACE loading in Ang II-Exos than in VSMCs, but significantly lower in GFP-Exos. Ang II-Exos promoted VSMC proliferation, migration, inflammation, and phenotypic switching, while GFP-Exos significantly reduced these effects by inhibiting ACE activity and regulating the NF-κB pathway. GFP effectively mitigated Ang II-induced VSMC dysfunction by modulating exosome-mediated ACE loading and phenotypic transformation.